Analysis of Influencing Factors Vertical Building Purchase Decisions: Case Study At Vida View Apartments Makassar - Nicko Limanta; Eric Harianto (Dinasti Publisher, 2024)
There are differences in the decision-making process in planning to buy an apartment when compared to the decision-making process for buying a landed house. Purchasing decisions that the company can know well are very useful for the company in determining the right marketing strategy so that it can produce optimal sales levels. This research aims to determine the factors that influence consumer decisions in the apartment purchasing process and how to implement them into sales strategies. The object of this research is Vida View Apartments in the city of Makassar. This research uses quantitative methods. Data collection in this research used a questionnaire with a population of 564 prospectives and previous buyers of Vida View Apartments. Sampling was carried out using a random sampling method with a total sample of 465 prospective and previous buyers. The analytical method used is exploratory quantitative using the SPSS application. From the results of this research, 5 new factors were formed that influence vertical building purchase decisions, namely, investment value and facilities, brand value, promotional strategy, social environment and ease of financing, with the most dominant new factor is investment value and facilities (55.026%). These findings can be used as a reference in formulating sales strategies, pricing strategies and promotional strategies for Vida View management or similar business in their efforts to increase sales.